Enriched-air/oxygen for pre-flight surface intervals - Leishman, Aren; Tillmans, Frauke; Buzzacott, Peter (2022)
Introduction: Current guidelines for pre-flight surface intervals (PFSI) of 12-18 hours represent a delay if urgent medevac is required. This study seeks to investigate the potential use of enriched air mixtures and oxygen to decrease PFSI.